1998
DOI: 10.1002/hep.510270211
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B injury, male gender, aflatoxin, and p53 expression each contribute to hepatocarcinogenesis in transgenic mice†

Abstract: The objective of the present study is to develop experimental models in mice to study the role of the four major risk factors for development of hepatocellular carcinoma (HCC) in humans. The major risk factors are: hepatitis B infection, male gender, aflatoxin exposure, and p53 gene loss or mutation. HCC is the predominant cause of cancer mortality of males in Sub-Saharan Africa and Southern China. 1-3 It causes 65% to 75% of all cancer deaths in males and 30% to 55% of cancer deaths in females in Mozambique a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 36 publications
4
57
1
Order By: Relevance
“…No tumors of any grade were found in groups VB (7 males and 6 females) and VIB (7 males and 5 females), and only 18% of the male mice (2/11) and 0/7 females in VIIB (HBsAg positive, p53ϩ/ϩ) expressing the p53ser246 mutant had tumors and these were grade I. In addition, in the previously reported study 21 of the ''control'' groups, 2/8 male HBsAg transgenic, p53ϩ/Ϫ male mice not treated with AFB1 did have grade II tumors. Thus, although the data are not definitive, expression of the mutant appears only to have a significant effect in AFB1-treated mice.…”
Section: Detection Of Mutant P53 Protein Expressionmentioning
confidence: 51%
See 1 more Smart Citation
“…No tumors of any grade were found in groups VB (7 males and 6 females) and VIB (7 males and 5 females), and only 18% of the male mice (2/11) and 0/7 females in VIIB (HBsAg positive, p53ϩ/ϩ) expressing the p53ser246 mutant had tumors and these were grade I. In addition, in the previously reported study 21 of the ''control'' groups, 2/8 male HBsAg transgenic, p53ϩ/Ϫ male mice not treated with AFB1 did have grade II tumors. Thus, although the data are not definitive, expression of the mutant appears only to have a significant effect in AFB1-treated mice.…”
Section: Detection Of Mutant P53 Protein Expressionmentioning
confidence: 51%
“…19,20 Because of the complexity of the data, the results of control groups of mice without the p53ser246 mutations are included in a separate report. 21 These are groups I to IV:…”
Section: Detection Of Mutant P53 Messenger Rna Using Reverse-transcrimentioning
confidence: 99%
“…Mouse liver tumors hardly contain any p53 mutations, even upon AFB 1 exposure, which led to the speculation that the nucleotide composition differences between mouse and human p53 genes could be one reason for the lack of mutations in mouse p53 in liver cancers. 29 However, the results presented here suggest that this may not be the case. Replacement of the whole DNA-binding domain in the mouse p53 locus with the human p53 counterpart in the Hupki mice has resulted in the generation of a valuable tool to study the mutagenic processes that occur in human cells upon exposure to carcinogens.…”
Section: Discussionmentioning
confidence: 54%
“…29 Further analysis using HBsAg transgenic mice demonstrated that although HBsAg and AFB 1 together were strongly carcinogenic, the presence of p53 mutation significantly enhanced the cocarcinogenic affect, thereby facilitating HCC formation. 29,37 These data raise the possibility that inactivation of p53 through mutations, such as found in AFB 1 -exposed individuals, may accelerate the adenoma to carcinoma transition. It is thus tempting to speculate that p53 mutations may be a late event that promotes carcinoma development in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, models based on the HBsAg transgenic mouse model of Chisari et al and the HBx transgenic mouse model of Kim et al [60] are commonly used to study mechanisms involved in hepatocarcinogenesis. These models are also applied to study possible synergistic relations between chemical carcinogens (such as aflatoxin B1 or diethyl nitrosamine) and HBV-infection [65][66][67] . Another application is the use of bitransgenic mouse models, in which mice are produced that are transgenic for a gene [48,68,69] .…”
Section: Hepatitis B Virus-associated Hccmentioning
confidence: 99%